The Effect of School-Year Employment on Cognitive Skills, Risky Behavior, and Educational Achievement. (June 2022) - Lesner, Rune Vammen; Damm, Anna Piil; Bertelsen, Preben; Pedersen, Mads Uffe
Highlights: Employment at age 15-16 fosters skill formation and reduces risky behavior Effects are identified in a value-added model exploiting variation within pairs of twins Work experience increases exit exam grades and reduces juvenile delinquency Work experience increases the years of schooling attained by age 20 If anything, work experience reduces school dropout and school absenteeism Abstract: We estimate the causal effect of hours of employment during the final year of compulsory school on cognitive skills, risky behavior, and educational achievement. The effect is identified by exploiting variation in hours of school-year employment between employed twins and estimation of a value-added model using administrative registers. Increasing hours of school-year employment increases grades in the school exit exams, reduces juvenile delinquency in the following year, and increases the years of schooling attained by age 20. If anything, increasing hours of school-year employment reduces school dropout and school absence. Our results are consistent with a non-linear effect of employment intensity on educational achievement and employment being preventive of risky behavior.